À la croisée du chemin Roxham et de la rhétorique politique : démystifier l’Entente sur les tiers pays sûrs - Mayrand, Hélène; Smith-Grégoire, Andrew (Revue de droit de l'Université de Sherbrooke, 2018)
The Agreement between the Government of Canada and the Government of the United States of America for cooperation in the examination of refugee status claims from nationals of third countries (Safe Third Country Agreement) has been subject to criticism since its adoption. Aimed at addressing asylum shopping, the agreement prevents asylum seekers, who have transited through one country, from applying for asylum in the other, subject to certain exceptions. The fact that the agreement applies only to land border ports of entry has led to an increase in irregular entries into Canada, particularly since 2017. The agreement has been the subject of numerous legal challenges. Against this backdrop, the authors analyze the implementation of the agreement in Canadian law and the issues it raises. They argue that the agreement is counterproductive, as if fails to effectively promote the orderly processing of refugee claims from the United States. They also examine the historical background of the numerous legal challenges to the agreement, including the latest Federal Court decision of 2020 which found that the agreement violates section 7 of the Canadian Charter of Rights and Freedoms.